2015
DOI: 10.1038/srep11706
|View full text |Cite|
|
Sign up to set email alerts
|

The Inhibition of the Rayleigh-Taylor Instability by Rotation

Abstract: It is well-established that the Coriolis force that acts on fluid in a rotating system can act to stabilise otherwise unstable flows. Chandrasekhar considered theoretically the effect of the Coriolis force on the Rayleigh-Taylor instability, which occurs at the interface between a dense fluid lying on top of a lighter fluid under gravity, concluding that rotation alone could not stabilise this system indefinitely. Recent numerical work suggests that rotation may, nevertheless, slow the growth of the instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 42 publications
(41 reference statements)
1
59
0
Order By: Relevance
“…The e↵ect of rotation on Rayleigh-Taylor instability was first considered by Chandrasekhar (1961), who concluded that it slows down the instability, and later extended by Tao et al (2013) to the nonlinear stage. These predictions have been confirmed by numerical simulations by Carnevale et al (2002) and more recently by the experiments by Baldwin et al (2015). The e↵ect of rotation on the turbulent phase is less clear.…”
Section: Rayleigh-taylor Turbulence In the Presence Of Rotationsupporting
confidence: 63%
See 3 more Smart Citations
“…The e↵ect of rotation on Rayleigh-Taylor instability was first considered by Chandrasekhar (1961), who concluded that it slows down the instability, and later extended by Tao et al (2013) to the nonlinear stage. These predictions have been confirmed by numerical simulations by Carnevale et al (2002) and more recently by the experiments by Baldwin et al (2015). The e↵ect of rotation on the turbulent phase is less clear.…”
Section: Rayleigh-taylor Turbulence In the Presence Of Rotationsupporting
confidence: 63%
“…In the case Figure 7 Rotating RT turbulence. The two images on the left show the evolution of the RT instability of a paramagnetic liquid (pink) above a diamagnetic liquid (clear) without rotation (upper) and with ⌦ = 4.6 rad s 1 (lower) (Figure taken from Baldwin et al (2015)). The two images on the right represent the temperature field, at the same time t = 20⌧ , for two simulations of the OB equations with the Coriolis force starting from the same initial condition, with ⌦ = 0 (left) and with ⌦⌧ = 20 (right) (⌧ = (Lz/Ag) 1/2 ).…”
Section: Rayleigh-taylor Turbulence In the Presence Of Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of RT convection, the effect of rotation has been studied more recently by means of both experiments (Baldwin et al 2015) and DNS within the Boussinesq approximation (Boffetta et al 2016). The main result is that rotation always reduces the turbulent heat transfer in this case.…”
Section: Introductionmentioning
confidence: 99%